2014
DOI: 10.1007/s40290-014-0059-1
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review to Identify the Use of Preference Elicitation Methods in Healthcare Decision Making

Abstract: Introduction Preference elicitation methods help to increase patient-centred medical decision making (MDM) by measuring benefit and value. Preferences can be applied in decisions regarding reimbursement, including health technology assessment (HTA); market access, including benefit-risk assessment (BRA); and clinical care. These three decision contexts have different requirements for use and elicitation of preferences. Objectives This systematic review identified studies using preference elicitation methods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 63 publications
0
50
0
Order By: Relevance
“…Relatively few studies have investigated using preference instruments in clinical practice. A recent review showed that 40% (n=134) of studies that utilized such methods were developed to be used in clinical decisions [5]. However, few have actually been tested in a healthcare setting.…”
Section: Why Conduct a Formal Assessment Of Individual Patient Prefermentioning
confidence: 99%
“…Relatively few studies have investigated using preference instruments in clinical practice. A recent review showed that 40% (n=134) of studies that utilized such methods were developed to be used in clinical decisions [5]. However, few have actually been tested in a healthcare setting.…”
Section: Why Conduct a Formal Assessment Of Individual Patient Prefermentioning
confidence: 99%
“…Oncologists required an average of six additional months of life for a cancer drug that costs $75,000, which implied an ICER of $100,000/QALY, and 7-8 months for a drug that costs $150,000, suggesting an ICER of $192,308/QALY [14]. Although these findings may not be generalizable across different healthcare systems, willingness to pay varies between stakeholders and across societies and invokes wider concerns than maximization of QALYs [11,12].…”
mentioning
confidence: 94%
“…This is made more pronounce by studies that show decisions on funding policies, which are supposed to reflect societal values, often differing [11], and that different stakeholders have different priorities and preferences [12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods can be used to elicit patient preferences including matching methods, conjoint analysis, and multicriteria decision analysis. Weernink et al [10] provided a comprehensive review of preference elicitation methods for regulatory decision making and concluded that matching methods and conjoint analysis fulfill the requirements to support regulatory decision making.…”
Section: Introductionmentioning
confidence: 99%